2022
DOI: 10.1111/head.14308
|View full text |Cite
|
Sign up to set email alerts
|

Most bothersome symptoms in patients with migraine: A hospital‐based study in Taiwan

Abstract: Objective: To investigate the distribution, clinical associations, and treatment responses for the most bothersome symptoms of migraine in a large sample of patients with migraine in Taiwan. Background:The most bothersome symptom is recently recommended as a co-primary endpoint in clinical trials of acute treatment of migraine. However, most clinical trials and observational studies have been conducted in the United States and Europe, with photophobia representing the most common most bothersome symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
3
1
Order By: Relevance
“…The present study found no significant association between migraine with aura and photophobia as the MBS. This is contradictory to the findings of a significant association between the two in the aforementioned Taiwanese study [ 7 ]. One possible reason for the discrepancy is the difference in the study settings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present study found no significant association between migraine with aura and photophobia as the MBS. This is contradictory to the findings of a significant association between the two in the aforementioned Taiwanese study [ 7 ]. One possible reason for the discrepancy is the difference in the study settings.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, only one Asian study has reported on the MBS in a population with migraine. A Taiwanese hospital study revealed that nausea was the most common MBS, followed by phonophobia and photophobia [ 7 ]. Our results are similar to those of this Taiwanese study, in that nausea was the most common MBS, followed by phonophobia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to unilateral, throbbing pain, many different non‐headache symptoms occur during or between migraine attacks (Headache Classification Committee of the International Headache Society [IHS], 2018 ; Tu et al., 2022 ). Several studies have examined the association between migraine and cognitive function (Chen & Wang, 2018 ; Karsan & Goadsby, 2021 ).…”
Section: Introductionmentioning
confidence: 99%